Influence of lipid content on methane production by anaerobic digestion of leachate from perishable waste resource utilization sites(油脂含量对易腐垃圾资源化利用站点渗滤液厌氧消化产甲烷的影响) - 唐航(TANG Hang); 秦勇(QIN Yong); 吴伟祥(WU Weixiang) (浙江大学学报. 农业与生命科学版)
In response to the notable characteristics of high lipid content and substantial fluctuations in leachate from perishable waste resource utilization sites, five different lipid content gradients of perishable waste leachate were set at 1.0, 2.5, 5.0, 10.0 and 15.0 g/L in this study to conduct an assessment to discern the influence of lipid content on methane production efficiency, substance degradation, and microbial community structure during anaerobic digestion (AD). The results revealed that within a specific concentration range, lipid content did not directly impede methane production in the leachate. As lipid content increased from 1.0 g/L to 15.0 g/L, the cumulative methane yield per unit chemical oxygen demand escalated from 81.36 mL/g to 91.29 mL/g. However, lipid degradation occurred over an extended period, with the initial 6 d primarily involving hydrolysis into long-chain fatty acids, followed by subsequent degradation into volatile fatty acids and then methane production. This prolonged degradation resulted in inadequate gas production from high-lipid-content leachate within the short retention time of 6 d and posed a risk of inhibition due to the presence of long-chain fatty acids. Moreover, lipid content significantly influenced the bacterial community structure during AD. On the 6th day of anaerobic fermentation, the relative abundance of the Oscillospiraceae family exhibited a substantial increase from 1.20% to 17.92% (P＜0.05) as lipid content escalated from 1.0 g/L to 15.0 g/L, playing a pivotal role in the degradation of leachate lipids and methane production. These findings offered crucial theoretical insights for developing technologies aimed at treating oily leachate from perishable waste resource utilization sites. . 针对易腐垃圾资源化利用站点渗滤液油脂含量高、波动大的特点，设置1.0、2.5、5.0、10.0、15.0 g/L 5个不同易腐垃圾渗滤液油脂含量梯度，评估油脂含量对渗滤液厌氧消化过程产甲烷效能、物质降解和微生物群落结构的影响。结果显示：在一定范围内，油脂含量对易腐垃圾资源化利用站点渗滤液厌氧产甲烷无直接抑制作用，随着油脂从1.0 g/L提升至15.0 g/L，单位化学需氧量（chemical oxygen demand, COD）累计产甲烷量从81.36 mL/g提升至91.29 mL/g。但油脂降解周期长，在发酵前6 d主要水解成长链脂肪酸（long-chain fatty acid, LCFAs），随后才进一步降解为挥发性脂肪酸并转化为甲烷，导致短停留时间（6 d）内高含油渗滤液产气不佳并存在长链脂肪酸抑制风险。油脂含量主要对厌氧产甲烷过程中细菌群落结构产生影响，在厌氧发酵第6天时随油脂含量提升（由1.0 g/L提升至15.0 g/L）颤螺旋菌科（Oscillospiraceae）细菌相对丰度由1.20%显著提升至17.92%（P＜0.05），在渗滤液油脂降解产甲烷过程中发挥着关键作用。这些发现为易腐垃圾资源化利用站点含油渗滤液处理技术的开发提供重要的理论参考。